THE CHALLENGED STATE SOVEREIGNTY: A REVIEW OF ELI CASE - Chen, Hongfan (PEOPLE: International Journal of Social Sciences, 2020)
Normally the intellectual property is defined as “asset” (Frankel, 2016, p. 21) in FTAs that allows the investors to protect their rights and interests when disputes arise. In 2010 and 2011, the Canadian courts made decisions that invalidated two patents protection on Strattera and Zyprexa, respectively. To protect its interests, Eli Lilly and Company brought a patent right dispute to ICSID in the late of 2012. According to the claims of Eli, the decisions of the Canadian courts can be deemed as the violation of Article 1110 (Expropriation) and Article 1105 (Minimum Standard of Treatment) of North American Free Trade Agreement (NAFTA). Although the Tribunal dismissed the claims of Eli in March 2017 eventually, the actions of Eli de facto challenged state sovereignty and decreased the discretion of Canada to define and regulate its internal intellectual property system (Billingsley, 2015, p. 27). This essay will first present a brief introduction of the Eli Lilly and Company v. Canada and will discuss the evaluation of the Tribunal’s decision in Part 2.